Urinary Excretion of Thiol Compounds in Patients with Rheumatoid Arthritis - Rojkovich, Bernadette (American Society for Microbiology, 1999)
The objective of the present study was to assess the excretion of urinary thiol compounds in patients with active and inactive rheumatoid arthritis (RA). Urinary thiol compounds were measured by the method of Kokonov (M. T. Kokonov, Lab. Delo 5:273–276, 1965) in 51 outpatients with active and inactive RA. Those with active disease had significantly higher levels of urinary thioamine excretion.